PECTIN AS A UNIVERSAL REMEDY IN THE FIGHT AGAINST COLORECTAL CANCER - Голотюк, В. В.; Попович, Л. О.; Доскалюк, Б. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
Colon cancer is one of the most common cancer globally. It occupy the fourth place in the structure of total cancer incidence. The basic treatment for colon cancer is surgery combined with chemotherapy or radiotherapy. Usually chemotherapy is provided by injection route. Alternative to the usual chemotherapy might be oral intake of chemotherapeutic agents. In this way can be achieved the reduce of drug dose, systemic side effects and increased. Pectin can be used as colon-specific drug delivery agent, because colonic microflora can selectively digest it. So this leads to the prevention of drug release in the upper gastrointestinal tract. Pectin can be considered not only as drug carrier but also as therapeutic agent for use in the prevention and fight against colon cancer.